Plastic chronic wound management with Cellutome - Seip, G. U. (Phlebologie, 2016)
Chronic wounds continue to present a significant challenge to health-care providers around the globe. Unlike acute wounds, chronic wounds do not proceed through an orderly process of repair. In recent years many new modalities of modern wound treatment systems have been promoted. However, until recently there were few modalities designed to promote epithelialisation of a fully granulated wound. Mesh graft procedures have long been the gold standard for the management of acute wounds and chronic wounds but have also many disadvantages like discomfort associated with the donor site and the creation of a second painful wound (donor site).The increase of chronical wounds in Germany due to the average age of patients, the aggressiveness of medical treatment and increase of numbers of patients with diabetes and severe polymorbidity requires specialized wound treatment and plastic surgery. Since 2014 there was a new innovative system introduced in the market called Cellutome epidermal harvesting system. The Cellutome system is a epidermal harvesting system for skin grafting and can replace in many cases the traditional meshgraft procedure with a classic dermatoma. The skin donor section on the patient`s thigh heals within days without scarring. The system offers a precise, simplified and minimal invasive option for skin grafting in the treatment of especially chronic wounds.
Keywords: Chronic wounds; Cellutome; skin grafting